Hydrated Sodium Ion Clusters [Na+(H2O)n (n = 1–6)]: An ab initio Study on Structures and Non-covalent Interaction - Wang, Pengju; Shi, Ruili; Su, Yan; Tang, Lingli; Huang, Xiaoming; Zhao, Jijun (Frontiers in Chemistry, 2019)
Structural, thermodynamic, and vibrational characteristics of water clusters up to six water molecules incorporating a single sodium ion [Na+(H2O)n (n = 1–6)] are calculated using a comprehensive genetic algorithm combined with density functional theory on global search, followed by high-level ab initio calculation. For n ≥ 4, the coordinated water molecules number for global minimum of clusters is 4 and the outer water molecules connecting with coordinated water molecules by hydrogen bonds. The charge analysis reveals the electron transfer between sodium ions and water molecules, providing an insight into the variations of properties of O–H bonds in clusters. Moreover, the simulated infrared (IR) spectra with anharmonic correction are in good agreement with the experimental results. The O–H stretching vibration frequencies show redshifts comparing with a free water molecule, which is attributed to the noncovalent interactions including the ion–water interaction and hydrogen bonds. Our results exhibit the comprehensive geometries, energies, charge and anharmonic vibrational properties of Na+(H2O)n (n = 1–6), and reveal deeper insight of noncovalent interactions.